Pengaruh Profitabilitas, Likuiditas dan Kepemilikan Manajerial Terhadap Pengungkapan Corporate Social Responsibility (CSR) pada Perusahaan Makanan dan Minuman Periode 2019-2021 - Fatimatuzzahro' Fatimatuzzahro'; Siti Alliyah (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
Disclosure of corporate social responsibility (CSR) is an action taken to encourage economic sustainability for businesses, government and local residents. The purpose of this study is to see how profitability, liquidity, and managerial ownership affect the CSR disclosure of food and beverage companies from 2019 to 2021. The selection method is used in data collection and secondary data sources. Sampling used purposive sampling because the research conducted was a quantitative study of 8 companies for 3 years. This study used IBM SPSS 22 software for data analysis with multiple linear regression. The results of this study indicate that profitability has no effect and is not significant on CSR disclosure, liquidity has a negative effect on CSR disclosure and managerial ownership has a positive effect on CSR disclosure.